Application of Stockwell Coherence To Prediction Of Alertness Under Anaesthesia - Akan, Aydın; Demiralp, Tamer; GÜRKAN, GÜRAY (Brno Univ Technology Vut Press, Purkynova 118, Brno 61200, Czech Republic, 2010)
In this paper, we represent an application of Stockwell Coherence to scalp EEG signals under anesthesia. By the analysis of overlapping, stationary data segments, we obtained the time-varying Stockwell coherence, which reveals the time evolution of coherence changes between any selected channel pair. After the injection and release of the anesthetic agent, time-varying Stockwell coherence analyses demonstrate similar characteristics for different patients.